Combining ability and gene action for agronomic traits and Fusarium wilt resistance in pigeonpea. Issue 6 (2nd November 2022) - Yohane, Esnart Nyirenda; Shimelis, Hussein; Laing, Mark; Mathew, Isack; Shayanowako, Admire
ABSTRACT: Combining ability analysis is fundamental in breeding programs to select desirable parents and progenies. The objectives of this study were to determine the combining ability effects, and gene action controlling agronomic traits and resistance to Fusarium wilt (FW) caused by Fusarium udum Butler in pigeonpea [ Cajanus cajan (L.) Millspaugh]. Twenty-five progenies were developed from 10 selected parents using a 5 × 5 North Carolina Design II. The progenies and their parents were assessed for agronomic traits and FW resistance. The genotypes were subjected to artificial FW infection using a root dip inoculation technique to evaluate seedling resistance. ICEAP 87105 and ICEAP 01285 had significantly negative general combining ability (GCA) effects for days to 75% maturity (DTM), whereas MWPLR 22, Sauma and Mwayiwathualimi had positive GCA effects for grain yield (GYD) in a desirable direction. The study selected the best hybrids such as ICEAP 01285 × MWPLR 14 for early maturity, FW resistance and a high GYD, and TZA 5582 × ICEAP 00554, TZA 5582 × MWPLR 14, and Mwayiwathualimi × MWPLR 22 for FW resistance and a high GYD. The narrow-sense heritability values varied from 27% (number of seeds per plant) to 97% (DTM). Parental lines TZA 5582 and MWPLR 14 made strong contributions to desirable gene combinations that improved agronomic traits in the selected crosses. The new hybrids form novel breeding populations useful in improving the traits of economic importance in pigeonpea.